Development of Hijaiyah Flashcard Media to Improve Alquran Reading and Writing Skills of Al-Istiqomah Santri Kedungpapar Sumobito Jombang - Yenny Ambarwati; Dhikrul Hakim; Siti Asiah (Indonesian Journal of Teacher Education, 2026)
The limited use of interesting and interactive learning media in learning to read and write the Koran at TPQ Al-Istiqomah Kedungpapar Sumobito Jombang causes students to be less motivated in the learning process. This research aims to develop hijaiyah flashcard media, test its feasibility, and analyze the effectiveness of its use in improving students' Al-Quran reading and writing skills. The research uses mixed research with the Research and Development (R&D) method with a 4D model which includes the define, design, development and disseminate stages. Data collection was carried out through observation, interviews, questionnaires, documentation and tests on 20 students. Data were analyzed descriptively qualitatively and quantitatively, followed by normality tests and paired sample t-tests. The results of the research show that the hijaiyah flashcard media was successfully developed according to learning needs, obtained a very appropriate category based on the validation results of media experts, material experts and practitioners, and was effective in improving students' reading and writing Al-Quran skills. The effectiveness of the media is shown by an increase in the average pre-test score from 52.50 to 82.50 in the post-test with a significance value of 0.000 (<0.05). Thus, hijaiyah flashcard media is suitable for use as a learning medium to improve Al-Quran reading and writing skills at TPQ.